2019
DOI: 10.3390/ijms20020246
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Cellular and Subcellular Localisation of Kv4.2 and Kv4.3 Channels in the Rodent Hippocampus

Abstract: The Kv4 family of voltage-gated K+ channels underlie the fast transient (A-type) outward K+ current. Although A-type currents are critical to determine somato-dendritic integration in central neurons, relatively little is known about the precise subcellular localisation of the underlying channels in hippocampal circuits. Using histoblot and immunoelectron microscopic techniques, we investigated the expression, regional distribution and subcellular localisation of Kv4.2 and Kv4.3 in the adult brain, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
7
22
1
Order By: Relevance
“…We found that roughly two-thirds of subunits were present in dendrites and one-third in axons (see Figure 3B and Table 1). Predominant dendritic segregation of the channel is corroborated by other localization studies (4,6,8,11) as well as our measure of transfected fluorescence intensity per unit area ( Figure 3C). To estimate rates from tot densities, we grouped mt and del compartments (from Figure 4Aii) to produce a model with only a tot and d tot , depicted in Figure S6B.…”
Section: Disparity Between Kv42 Static Localization and Mobile Frequsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that roughly two-thirds of subunits were present in dendrites and one-third in axons (see Figure 3B and Table 1). Predominant dendritic segregation of the channel is corroborated by other localization studies (4,6,8,11) as well as our measure of transfected fluorescence intensity per unit area ( Figure 3C). To estimate rates from tot densities, we grouped mt and del compartments (from Figure 4Aii) to produce a model with only a tot and d tot , depicted in Figure S6B.…”
Section: Disparity Between Kv42 Static Localization and Mobile Frequsupporting
confidence: 90%
“…This implies that increased dendritic demand and surface absorption of Kv4.2 depletes dendritic microtubule-bound subunit density, with axons obeying to opposite trend. Importantly, previous localization studies as well as our own observations reveal a non-negligible density of axonal Kv4.2 (8,11). With no known presynaptic function, this axonal fraction might be an artifact of mass action, as our study suggests.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Using subtype-specific monoclonal and polyclonal antibodies, we recently found that Kv4.2 and Kv4.3 subunits exhibit differential expression and distribution patterns in rodent hippocampus [ 24 ]. Here, using monoclonal antibodies against auxiliary KChIP3 and KChIP4 subunits, together with the antibodies against Kv4.2 and Kv4.3 subunits, we have now investigated the distribution of these molecules in the cerebellum using light microscopy immunohistochemical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Although the expression of A-type potassium condutcances in DG granule cells has been established through several lines of evidence (Beck et al, 1992;Sheng et al, 1992;Serodio and Rudy, 1998;Varga et al, 2000;Rhodes et al, 2004;Ruschenschmidt et al, 2006;Monaghan et al, 2008;Peng et al, 2013;Alfaro-Ruiz et al, 2019), heterogeneities in the impact of acutely eliminating A-type potassium channels have not been systematically assessed. Future studies should employ different techniques to acutely eliminate A-type potassium channels to assess potential heterogeneities of such elimination on neuronal firing rates.…”
Section: Heterogeneities In Ion Channel Regulation Of Neuronal and Nementioning
confidence: 99%